Synced ads: effects of mobile ad size and timing - Brechman, Jean M.; Varan, Duane; Wooley, Brooke; Bellman, Steven (Frontiers in Communication, 2024)
Introduction Synced ads differ from other forms of targeted advertising on mobile devices because they target concurrent media usage rather than location or predicted interest in the brand. For example, a TV-viewer’s smartphone could listen to the ads playing on the TV set and show matching social media ads. These social media ads could be timed to appear simultaneously with the TV ad, or shortly before or after. Methods This research reports a meta-analysis (N = 980) of four lab studies that used representative samples of consumers and realistic manipulations of synced ads. These studies contrasted with most previous studies of synced ads, which have used student samples and unrealistic manipulations or imagined scenarios, which means little is known about whether or why synced ads are effective in real life. These four studies manipulated the effects of synced-ad timing (simultaneous vs. sequential before or after) and the size of the mobile ad, to see if these moderate the effects of synced ads. Results The results showed that synced ads were more effective, measured by unaided brand recall, when they were shown after the TV commercial, rather than simultaneously. Ad size had no moderating effect, which suggests that normal ads can be used, rather than the full-screen or pop-up ads used in previous studies. A final study, in which ad timing was user-controlled, rather than advertiser-controlled, showed that precise timing is not important for synced-ad effectiveness. Discussion These results suggest the effects of synced ads are best explained by repetition rather than synergy between the two exposures. There were no significant effects on brand attitude, ad liking, or purchase intention. These results have implications for theoretical models of synced-ad effectiveness, and for advertisers planning to use synced ads.